Price competition in an inflationary environment - Dürsch, Peter; Eife, Thomas A. (Journal of monetary economics, 2019)
In an experimental study with price-setting firms we find that inflation significantly reduces real prices (by lowering price markups) and significantly raises welfare compared to the treatment with a constant overall price level. Money illusion and a reduced ability to collude in an environment with a constantly changing, i.e., increasing, price level drive this result. In a third treatment with deflation, collusion is somewhat reduced as well, but money illusion pushes prices up so that welfare is lower than under inflation.
Available online 20 November 2018
Gesehen am 09.08.2019